Dalam dekap serdadu: pergundikan di tangsi militer, 1872-1913 - Mutia Zaskia Nasution; Kurniawati Kurniawati; M. Hasmi Yanuardi (Historiography: Journal of Indonesian History and Education, 2022)
This article aims to highlight the life of concubines in the military world in the Dutch East Indies in the period 1872-1913 and to present various views of the pros and cons that made this practice considered quite controversial at its time. In order for the objectives of this research to be carried through, the author applied historical research method which has five stages consisting of topic selection, heuristics, verification, interpretation, and historiography. By using primary and secondary sources in the form of contemporary newspapers, documents, books, and articles relevant to the research theme. The practice of concubinage within the military barracks could not be separated from the establishment of an army under the name of Koninklijk Leger in the early 19th century. This practice was used to be associated with demoralization and also believed to be the source of several health issues amongst the soldiers, as well as encouraging the birth of a white proletariat class in the colonies, this leads to mixed opinions regarding the relationship between these two different races. This commotion prompted the colonial government to issue several policies, one of which was to increase military morale. After all, the concubine of tangsi is considered very detrimental, this practice indirectly joined a mixed society group known as the Indo group, where this group later helped support Indis culture in the Dutch East Indies.  Penulisan artikel ini bertujuan untuk menyoroti kehidupan pergundikan dalam dunia militer di Hindia Belanda pada periode 1872-1913 serta menampilkan berbagai pandangan pro dan kontra yang membuat praktik ini dianggap cukup kontroversial pada masanya. Dalam upaya untuk mencapai tujuan penelitian secara lengkap sesuai dengan permasalahan yang dibahas, penulis menggunakan metode penelitian sejarah yang terdiri dari lima tahapan meliputi pemilihan topik, heuristik, verifikasi, interpretasi, dan historiografi. Dengan menggunakan sumber primer dan sekunder yang berupa surat kabar sezaman, dokumen, buku, serta artikel yang relevan dengan tema penelitian. Praktik pergundikan tangsi tidak lepas dari pembentukan suatu pasukan ketentaraan yang bernama Koninklijk Leger pada awal abad ke-19. Praktik ini selalu dikaitkan dengan demoralisasi dan juga diyakini sebagai penyebab munculnya masalah kesehatan di antara para serdadu, serta mendorong lahirnya kelas proletariat kulit putih di tanah koloni yang membuat hubungan antar dua ras berbeda ini tidak jarang mengundang perdebatan di masyarakat. Kegaduhan tersebut membuat pemerintah kolonial pada akhirnya mengeluarkan beberapa kebijakan, salah satunya meningkatkan moral militer. Betapa pun pergundikan tangsi dianggap menuai banyak dampak merugikan, praktik ini secara tidak langsung turut sebuah golongan masyarakat campuran yang dikenal dengan golongan Indo, di mana kelompok ini nantinya turut mendukung kebudayaan Indis di Hindia Belanda.